Digital libraries: implementing strategies and sharing experiences (Springer, 2005)
This book constitutes the refereed proceedings of the 8th International Conference on Asian Digital Libraries, ICADL 2005, held in Bangkok, Thailand in December 2005. The 40 revised full papers, 15 revised short papers, and 15 posters presented together with 5 keynote and invited papers were carefully reviewed and selected from a total of 164 submissions. The papers are organized in topical sections on concepts and models for digital library systems, case studies in digital libraries, digital archives and museums, multimedia digital libraries, information processing in asian digital libraries, digital libraries for community building, information retrieval techniques, ontologies and content management in digital libraries, information integration and retrieval technologies in digital libraries, information mining technologies in digital libraries, digital library system architecture and implementations, information processing in digital libraries, human-computer interfaces, and metadata issues in digital libraries